2020
DOI: 10.1002/1878-0261.12758
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal activation of Hedgehog signaling establishes an immunosuppressive microenvironment in basal cell carcinoma by modulating skin immunity

Abstract: Activation of hedgehog/glioma‐associated oncogene homolog (HH/GLI) signaling induces basal cell carcinoma (BCC) and establishes an immunosuppressive tumor microenvironment. HH/GLI signaling inhibits the activity of antitumoral T cells via programmed death ligand 1/programmed death‐1 immune checkpoint signaling and the recruitment of immunosuppressive regulatory T cells. BCCs also show strong infiltration with antitumoral neutrophils. The data support the evaluation of combination treatments with HH inhibitors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 77 publications
1
22
0
Order By: Relevance
“…Hh and canonical or non-canonical Wnt signaling induce the expression and activation of immune checkpoint molecules such as PD-1/PDL-1 and CTLA-4 on CD8+ T cells. Thus, studies suggest that Shh and Wnt pathways support resistance to ICIs by maintaining the expression and activation of immune checkpoint molecules [ 31 , 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hh and canonical or non-canonical Wnt signaling induce the expression and activation of immune checkpoint molecules such as PD-1/PDL-1 and CTLA-4 on CD8+ T cells. Thus, studies suggest that Shh and Wnt pathways support resistance to ICIs by maintaining the expression and activation of immune checkpoint molecules [ 31 , 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our group and others have previously demonstrated that Shh pathway is associated with resistance to several anti-tumor therapies [ 26 ] such as chemotherapy [ 27 , 28 ], Tyrosine Kinase Inhibitors (TKIs) [ 29 ] and radiotherapy [ 30 ]. Like Wnt signaling, Shh pathway is also involved in the development and the activation of the immune response [ 31 , 32 , 33 ]. In gastric cancer, hedgehog signaling supports the expression of PD-L1 and tumor cell proliferation [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previously described ( 21 ), IHC and the immunoreactive score of SLC1A4 (proteintech, 13067-2-AP, 1:100) were conducted on the formalin-fixed and paraffin-embedded tissue sections.…”
Section: Methodsmentioning
confidence: 99%
“…In naïve T-cells, Hh pathway activation again reduces TCR signaling to inhibit proliferation and activation on TCR/CD28 ligation (9,11,12), but also influences many aspects of T-cell differentiation. In addition to promoting CD4+ Th2 effector differentiation in vitro and in allergic airways disease (4, 10), Hh signaling has been shown to drive CD8+ cytotoxic T cell (CTL) differentiation in vitro (13) and to promote NKgd T-cell differentiation and CD4+ regulatory T-cell (Treg) differentiation and function in vivo and in vitro (14)(15)(16)(26)(27)(28). Consistent with its role in Tregs, in many tissues Hh signaling has been shown to have anti-inflammatory action (15,(29)(30)(31)(32)(33)(34)(35), in contrast to its well-known pro-inflammatory role in allergic asthma (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%